Monitorization of Asymmetric Dimethylarginine (ADMA) Levels in an Experimental Ischemia-Reperfusion Flap Model: A Preliminary Report - Karaaslan, Onder; Sonmez, Erhan; Kankaya, Yuksel; Silistreli, Ozlem Karatas; Can, Murat Melih; Bedir, Yagmur Kaan; Caliskan, Gorkem (Journal of Reconstructive Microsurgery, 2013)
One of the most important endothelium-derived vasoactive mediators is nitric oxide (NO). Endothelial dysfunction by the loss of NO is a critical event during ischemia. Asymmetric dimethylarginine (ADMA) is a competitive inhibitor of NO synthase (NOS) that inhibits vascular endothelial NO production in concentrations found in pathophysiological conditions. The goal of this study was to monitorize overexpression of ADMA in an experimental ischemia-reperfusion flap model. This study was performed using 20 rats. The baseline ADMA levels were measured preoperatively. In Group I (n = 10, control) abdominal flaps were harvested and replaced in situ without creating ischemia. The plasma ADMA levels were measured at 1, 12, and 24 hours postoperatively. In Group II (n = 10, study) abdominal flaps were harvested, and clamping the vascular pedicle created a subsequent 8-hour period of warm ischemia. Clamps were removed and provided tissue reperfusion. The ADMA levels were taken after 1 hour of reperfusion, and at 12th and 24th hours. The mean preoperative ADMA levels in group I and group II were calculated to be 0.37 ± 0.06 (µmol/L) and 0.40 ± 0.06 (µmol/L), respectively. The differences between the preoperative ADMA levels were not statistically significant (p > 0.05). The mean postoperative ADMA levels in group I (control) were calculated to be 0.39 ± 0.09 (µmol/L) at the first hour, 0.42 ± 0.07 (µmol/L) at the 12th hour, and 0.40 ± 0.08 (µmol/L) at the 24th hour. Respectively, the mean postoperative ADMA levels in group II were calculated to be 0.68 ± 0.14 (µmol/L) after 1 hour of reperfusion, 0.62 ± 0.09 (µmol/L) at the 12th hour, and 0.60 ± 0.12 (µmol/L) at the 24th hour. All postoperative ADMA levels were significantly higher in Group II (p < 0.05). These experimental results suggest that systemic production of ADMA is greater in animals having ischemia reperfusion injury of the skin flaps. The strategy of decreasing levels of ADMA may be beneficial to prevent ischemia-reperfusion injury of flaps or composite transplants; thus, ADMA might be an important candidate of therapeutic target in flap or transplantation surgeries.
Keywords: asymmetric dimethylarginine; flap; ischemia reperfusion